2015
DOI: 10.1136/bcr-2015-211455
|View full text |Cite
|
Sign up to set email alerts
|

Functional movement disorder: a long journey to diagnosis

Abstract: SUMMARYA 61-year-old man presented to a country clinic with involuntary orofacial movements and progressive cognitive decline, causing significant disability and psychosocial distress. Review of records uncovered a 7-year history of presentations to several specialties, including memory clinics, neurology, internal medicine and emergency departments, with varied symptoms, extensive complex work up and inconclusive diagnosis. Comprehensive review at our hospital highlighted inconsistent neurological signs, fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Only 10 studies captured health domains, such as degree of disability, cognitive, emotional, and quality of life with specific tools. 11,14,16,19,[32][33][34][41][42][43] Degree of disability was most commonly captured with the Functional Independence Measure (FIM) (n = 3) 14,32,34 and Modified Rankin Scale (mRS) (n = 2). 16,33 Impact on quality of life was assessed using the health-related quality of life scale in two studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 10 studies captured health domains, such as degree of disability, cognitive, emotional, and quality of life with specific tools. 11,14,16,19,[32][33][34][41][42][43] Degree of disability was most commonly captured with the Functional Independence Measure (FIM) (n = 3) 14,32,34 and Modified Rankin Scale (mRS) (n = 2). 16,33 Impact on quality of life was assessed using the health-related quality of life scale in two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up symptoms were described in a total of 78 chronic patients (follow-up pooled mean 12.7 months), 14 acute patients (follow-up mean 18.0 months, median 8 months), and 60 unspecified patients (follow-up pooled mean 13.2 months). 11,16,19,[22][23][24][25]28,[32][33][34][35][36][37][38][39][40][41][42]44 A total of 16 chronic patients (18% of patients with reported follow-up) had a recurrence of symptoms in the follow-up period ranging from 1 month to 2.5 years. 34,37,38,40,44 Jacob et al (2018) reported eight patients that either had no change in symptoms or worsening symptoms at 6 months, but did not distinguish how many of these patients were relapses or nonresponders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations